2022
DOI: 10.7759/cureus.30206
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibody (ANCA)-Associated Renal Vasculitis Following COVID-19 Vaccination: A Case Report and Literature Review

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an immune-mediated disorder of small and medium-sized vessels, characterized by the production of autoantibodies that target the neutrophilic antigens leading to mononuclear cell infiltration and destruction of blood vessels in lungs, skin, and kidneys. Although rare, the coronavirus disease 2019 (COVID-19) vaccine may trigger autoimmune vasculitis. We report a rare case of ANCA-associated renal vasculitis following COVID-19 vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…AAV is classified into three types based on clinical features, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA) [ 111 ]. A total of 17 new-onset AAV cases have been reported, including 5 cases of PR3-ANCA vasculitis, 9 cases of MPO-ANCA vasculitis, and 3 cases of dual-positive MPO- and PR3-ANCA vasculitis [ [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. The majority of cases were women (11/17, 64.7%).…”
Section: Resultsmentioning
confidence: 99%
“…AAV is classified into three types based on clinical features, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA) [ 111 ]. A total of 17 new-onset AAV cases have been reported, including 5 cases of PR3-ANCA vasculitis, 9 cases of MPO-ANCA vasculitis, and 3 cases of dual-positive MPO- and PR3-ANCA vasculitis [ [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. The majority of cases were women (11/17, 64.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding COVID-19 vaccination, the toll-like receptor used as an adjuvant has the potential to induce SLE flares, upregulating the type I interferon pathway 25 . Several autoimmune phenomena have been described following vaccination, such as ANCAassociated vasculitis 26 , myositis 27 , autoimmune hemolytic anemia 28 , and thrombocytopenic purpura 29 , among others. However, the existing data is mostly based on case descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine may activate a cascade of pathways through dendritic and bone marrow cell stimulation, leading to autoinflammation [36,50,51]. Moreover, a series of cases showed that some patients developed dual-positive anti-GBM and MPO ANCA glomerulonephritis after mRNA COVID-19 vaccination, with outcomes varying from complete remission to dialysis dependence or death [5,52].…”
Section: Glomerulonephritis Associated With Anca Following Vaccinatio...mentioning
confidence: 99%
“…Thammathiwat and colleagues in their study emphasized the need to avoid unnecessary booster doses of COVID-19 vaccines in highrisk patients (carriers of HLA-DR4 or DRB4 alleles) [48,55]. Renal vasculitis induced by the COVID-19 vaccine is rare, and mass vaccination against COVID-19 infection globally is the appropriate strategy to combat this serious viral disease [5]. Table 4 summarizes the published cases of ANCAassociated renal vasculitis after COVID-19 vaccination [55].…”
Section: Glomerulonephritis Associated With Anca Following Vaccinatio...mentioning
confidence: 99%
See 1 more Smart Citation